The Impact of Digitalization of Services on Patient Satisfaction - Rofik darmayanti; Endah Luqmanasari; Takariningsih Dwi N; Endra Widiyanto; Kurniawan Edi Priyanto (Journal of Hospital Management and Services, 2026)
Background: Digital transformation in the healthcare sector aims to improve operational efficiency and service quality. However, challenges in system readiness and users' digital literacy can affect patients' perceptions of the service. Objective: This study aims to determine and analyze the effect of service digitalization on patient satisfaction at [Name of Healthcare Institution]. Methods: This study used a quantitative approach with a causal associative design. Sampling was conducted using a purposive sampling technique with a total sample of 50 patient respondents. Primary data were collected through questionnaires with a 5-point Likert scale. Data analysis techniques included instrument testing (validity and reliability), classic assumption testing (normality and heteroscedasticity), simple linear regression analysis, hypothesis testing (t-test), and the coefficient of determination (R2) using SPSS software. Results: The regression analysis resulted in the equation Y = 10.150 + 0.712X. The t-test showed that service digitalization had a positive and significant effect on patient satisfaction (t-count } 5.124 > t }2.011; t 0.000 < 0.05). The coefficient of determination (R2) value was 0.358, indicating that 35.8% of patient satisfaction was influenced by service digitalization, while the remaining 64.2% was influenced by other variables outside this research model. Conclusion: The implementation of service digitalization is empirically proven to significantly increase patient satisfaction. Time efficiency is the main driver of satisfaction, especially for the productive age group. Management is advised to maintain system stability and provide assistance officers for patients with limited digital literacy. Keywords : digitalization, health services, patients